(untitled) (Tạp chí Y học Cộng đồng, 2025)
Introduction: Patient Safety Culture (PSC) is one of the priorities for intervention in the healthcare environment aimed at the principle of “doing no harm to patients”. This study aims to assess the current situation of PSC at Long An General Hospital, Long An Province, in 2023. Methods: We applied a cross-sectional design to conduct online, self-administered interviews with all 187 health providers at Long An General Hospital. We used HSOPSC-VN2015 to evaluate the PSC of the hospital. Findings: The positive response rate of PSC was 71.4%. Out of the total 12 dimensions of PSC, six dimensions achieved a positive rate of 75% or higher. In contrast, the three dimensions with the lowest positive response rate were Staffing (56.1%), Nonpunitive Response to Error (55.6%), followed by Communication Openness (61.3%). Conclusion: The positive rate of PSC was 71.4% at Long An General Hospital. The study results recommend strengthening training and providing knowledge about PSC for all health staff, especially new staff; improving hospital infrastructure, including medical facilities and equipment; and developing a policy to support medical error reporting.